Estrategias de fidelización para mejorar la preferencia de los clientes de la empresa de transportes TUNESA - Huamachuco - Rodriguez Pizan, Charito (2016)
The company Transportes TUNESA is an organization dedicated to the heading of transport of passengers and shipping of parcels, belongs to Negreiros Group, and its main destinations the cities of Huamachuco, Santiago de Chuco, Trujillo and Lima, its official address is in the city Lima, Av Paseo de la Republica No. 1011 -. La Victoria, has local strategically located in each destination city. The research uses descriptive Methodology Research Type: Applied, not experimental and descriptive, inductive-deductive method, hypothetical-deductive method and the analysis-synthesis method was used, the survey as a research technique was also used. Companies dedicated to turning passenger, have multiple problems that should be addressed as a priority, such as counting units to ensure good service, convenient times, personalized attention, accident insurance, passenger safety, respect for regulations transportation, competitive drivers, rotating schedule for all staff, among others; the informal practice is a latent danger affecting formal firms, and in the field of transport is evident to a greater extent as the main competition TOURISM NEGREIROS or TUNESA are informal enterprises, for this reason the search for loyalty strategies is a priority for the company TUNESA. For this investigation has been taken as population, customers of the company TUNESA, to which they will direct the various strategies that will come up in the search to capture a larger number of customers as well as retain their buying behavior .